Levels of Matrix-Degrading Enzymes and Lubricin in Patients With Degenerative Joint Disease Requiring Arthroplasty. (January 2018) - Wanderling, Christopher; Liles, Jeffrey; Davis, Elissa; Schmitt, Daniel; Statz, Stephen; Guler, Nil; Hoppensteadt, Debra; Fareed, Jawed; Hopkinson, William
Total joint arthroplasty (TJA) of the hip or knee (THA and TKA) is the primary surgical intervention for individuals with degenerative joint disease (DJD). Although it is commonly thought that shear force on the joint causes the degradation of articular cartilage, it is possible that there are other factors that contribute to the progression of DJD. It is plausible that specific enzymes that degrade the joint are upregulated, or conversely, there is downregulation of enzymes critical for joint lubrication. The aim of this study is to profile collagenase-1, elastase, heparanase, and lubricin levels in patients undergoing TJA in order to determine potential preexisting dysregulation that contributes to the pathogenesis of DJD. Deidentified blood samples were obtained from patients undergoing TJA 1 day pre- and 1 day postoperatively. Plasma samples were analyzed using enzyme-linked immunosorbent assay kits for elastase, collagenase-1, heparanase, and lubricin. In comparison to healthy controls, there were significant increases in circulating collagenase-1, elastase, and lubricin levels in both the preoperative and postoperative samples. There were no significant differences in heparanase levels in the preoperative or postoperative samples. Comparing the preoperative versus postoperative patient samples, only lubricin demonstrated a significant change. The results of this study confirm that patients undergoing TJA have preexisting alterations in the levels of matrix-degrading enzymes and lubricin. The alterations observed in this study may provide insight into the pathogenesis of DJD.